Indeks Massa Tubuh yang Lebih Tinggi Berkaitan dengan Peningkatan Kelangsungan Hidup Secara Keseluruhan pada Pasien Kanker Ginjal: Tinjauan Sistematis dan Meta-analisis: Tinjauan Sistematis - Munawwir, Abdul; Adhani, Zalsabila Tiara; -, Aristo (Cermin Dunia Kedokteran, 2026)
Introduction: Obesity is linked to better oncological outcomes for renal cell carcinoma (RCC), despite being a well-known risk factor for many diseases. This article assesses the relationship between kidney cancer outcomes (overall survival/OS) and body mass index (BMI). Methods: PubMed, Medline, Embase, CINAHL, and Central were used to retrieve studies. Research published up to December 2024 is included in this review. The review was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. The quality of the study was assessed with the Newcastle-Ottawa Scale (NOS). RevMan version 5.4.1 was used to analyze and evaluate data. Results: Seven retrospective studies (HR 0.80, 95% CI 0.70–0.93, p = 0.03) showed that the group with normal BMI had a significantly lower overall survival rate than the group with obese or overweight BMI. Obesity may improve kidney cancer treatment outcomes, but the pathophysiology is not yet clear. Some studies suggest that overweight or obese individuals often have higher cancer biology, as they have lower levels of metabolic genes and fatty acids, which are important factors in tumor development. Healthy nutrition can also protect against treatment-related stress or make treatment work better. Conclusion: Obese or overweight individuals with kidney cancer had better results. Conversely, underweight group had more negative consequences.